Noise exposure assessment in the Poudre Fire Authority - Schwennker, Catherine, author; Brazile, William, advisor; Sandfort, Delvin, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2011)
According to the National Institute for Occupational Safety and Health (NIOSH), it is estimated that 22 million workers are exposed to hazardous levels of noise. Firefighters are part of this population of workers that are at potential risk of overexposure to such noise and subsequent noise-induced hearing loss. In fact, one NIOSH study found that 53 of 56 (96%) firefighters had detectable hearing loss. To ascertain the sources of firefighter noise exposures, noise samples were taken at ten Poudre Fire Authority stations on the equipment and emergency vehicles using a sound level meter. Results indicated that five of the six pieces of equipment located at the stations exceeded 85 dBA; and 13 of the 15 pieces of equipment on the trucks exceeded 85 dBA. Equipment that exceeds 85 dBA is important to identify since hearing loss can begin to occur at these levels. Code-3 operations that involve fire truck siren were measured at 92 dBA, and the operation of truck pumps at "high" psi was measured at 91 dBA. A 24-hour noise dose to firefighters was estimated to be at 48% of the OSHA permissible exposure limit. According to the OSHA Occupational Noise Control Standard, engineering controls are required to lower the noise levels below the eight-hour permissible exposure limit or hearing protection must worn when engineering controls are not feasible. Given the variability in the time of use of relatively loud firefighting equipment and the difficultly of measuring full-shift firefighter noise exposures, it is recommended that hearing protection be worn to help reduce the risk of noise induced hearing loss.